VIGOR TESTS FOR CARROT SEEDS - LIMA, Cristina Batista; ATHANÁZIO, João Carlos (Scientia Agraria, 2009)
This work had the purpose to compare the efficiency of vigor tests for evaluation of physiological quality of carrot seeds, ranked for size and stored by different periods. Six lots of carrot seeds from ‘Londrina’ population were tested for germination, tetrazolium, accelerated aging traditional, accelerated aging modified and seedling emergency. The seedling emergence test is distinguished in classification the lots by the vigor differences. The combination salt solution with 48 or 72 h of exposure is adjusted for the accelerated aging test. The seeds of larger size have higher physiological quality to smaller.